Evaluasi Usability Aplikasi Mobile Cicil.co.id dengan menggunakan Metode Heuristic - Chintia Devi; Buce Trias Hanggara; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cicil or Cicil.co.id is a social-tech financial startup company which provide ease in installments for students. But Cicil mobile applications for android have not been able to meet the requirements of its users as we saw on Google Play Store's review from July to August 2019 and the results of interviews with three users. Some of the problems in Cicil applications were from usability aspect. Bad experienced by these users make users unsatisfied with the use of the Cicil mobile application and it cause users give low ratings for the Cicil mobile application. This research was conducted with a deeper purpose regarding the usability aspects related to the Cicil application by using the heuristic method. After that, recommendations are given on the usability problems. The recommendations were based on advice from evaluator, guidelines, previous applications, journal, article, or book. This study used four evaluators in the regular category and found 27 problems included 10 Nielsen's heuristic principles. The highest precentage of problems found on heuristics number 6 and 7 is 14,52%, while the lowest percentage of heuristic numbers is provided in heuristic number 9 is 3,22%. After going through the analysis, from 27 usability promblems only 21 problems were given recommendations for improving the application interface. Six problems were not given recommendations because they were not in accordance with the existing principles and theories.